Development of an Integrated Library Management System (ILMS) - Ayo, Eliza B.; Jotic, Rommel N.; Raqueño, Avelina; Loresca, John Vincent G.; Mendoza, Irene F.; Baroña, Princess Vanessa M. (International Journal of Interactive Mobile Technologies (iJIM), 2023)
Abstract— This document presents the design and development of an integrated library management system based on the needs assessment conducted in response to technology, infrastructure, existing condition, facilities, technology readiness of human resources, automation sufficiency level, and support of technical staff among ninety-eight (98) respondents using the descriptive developmental method. Developing a system based on research is crucial in ensuring the accuracy and reliability of the system. This approach addresses specific problems or challenges by incorporating evidence-based practices and the latest advancements in the field. The findings include the need to mentor the respondents on how to use technology and the influence of others as a factor in using technology. There is a difficulty encountered in navigating schools’ virtual libraries, unavailability of materials, and visiting it is not enticing anymore since information is available from the internet. The rarity of introducing new technology and the absence of 3D printers are common pain points. However, improvements on the library website, email/chat with a librarian, online research guides, online book reservations, and book delivery service were noticed. Research gaps and recommendations from the selected Library Management System were also employed as additional input in the development of the system. A deeper understanding of the Internet of Things, Artificial Intelligence, Big Data, Robotics, and Embedded Systems through training, webinars, and workshops are necessary for the librarian. These technologies could be applied in library operations and transactions. Procurement of the latest equipment which includes 3D printers and the development of integrated library systems are steps to take to improve the library's services and operation. By combining the results of assessments and incorporating new knowledge derived from research gaps and recommendations, provided a stronger foundation for the system. It also provides validation and grounding in scientific principles, ensuring that the system is well-informed and effective in its implementation. Ultimately, developing a system based on research leads to more informed and effective solutions to pain points and challenges.